Preparation, characterization and release profiles of insulin-loaded double-walled poly(lactide-co-glycolide) microspheres - Rahman, Md. Mokhlesur; Ansary, Rezaul Haque; Katas, Haliza; Ab. Hadi, Hazrina; Mohamed, Awang (2015)
The aim of this study was to fabricate insulin-loaded double-walled poly(lactide-co-glycolide) (PLGA) microspheres using two different terminated PLGA (hydroxyl and carboxyl) to reduce the initial burst release as well as to remove the lag phase from the release profiles of insulin loaded PLGA microspheres. Double-walled microspheres were prepared by a modified water-in-oil-in-oil-in-water (w/o/o/w) emulsion solvent evaporation method. The prepared double-walled microspheres were non-porous, smooth surfaced, and spherical in shape. A significant reduction of the initial burst release of insulin was achieved from the prepared double-walled microspheres. Moreover, a sustained and complete release of insulin without any lag phase was achieved in this study. Thus, double-walled microspheres can be a potential delivery system of therapeutic insulin.